Catheter Ablation of Atrial Fibrillation: State of the Art and Future Perspectives - Rottner, Laura; Bellmann, Barbara; Lin, Tina; Reissmann, Bruno; Tönnis, Tobias; Schleberger, Ruben; Nies, Moritz; Jungen, Christiane; Dinshaw, Leon; Klatt, Niklas; Dickow, Jannis; Münkler, Paula; et al. (Cardiology and Therapy, 2020)
Purpose of Review Atrial fibrillation (AF), the most common sustained arrhythmia, is associated with high rates of morbidity and mortality. Maintenance of stable sinus rhythm (SR) is the intended treatment target in symptomatic patients, and catheter ablation aimed at isolating the pulmonary veins provides the most effective treatment option, supported by encouraging clinical outcome data. A variety of energy sources and devices have been developed and evaluated. In this review, we summarize the current state of the art of catheter ablation of AF and describe future perspectives. Recent Findings Catheter ablation is a well-established treatment option for patients with symptomatic AF and is more successful at maintaining SR than antiarrhythmic drugs. Antral pulmonary vein isolation (PVI) as a stand-alone ablation strategy results in beneficial clinical outcomes and is therefore recommended as first-line strategy for both paroxysmal and persistent AF. While radiofrequency-based PVI in conjunction with a three-dimensional mapping system was for many years considered to be the “gold standard”, the cryoballoon has emerged as the most commonly used alternative AF ablation tool, especially in patients with paroxysmal AF. Patients with persistent or long-standing persistent AF and with arrhythmia recurrence after previous PVI may benefit from additional ablation strategies, such as substrate modification of various forms or left atrial appendage isolation. New technologies and techniques, such as identification of the AF sources and magnetic resonance imaging-guided substrate modification, are on the way to further improve the success rates of catheter ablation for selected patients and might help to further reduce arrhythmia recurrence. Conclusions Pulmonary vein isolation is the treatment of choice for symptomatic patients with paroxysmal and persistent drug-refractory AF. The reconnection of previously isolated pulmonary veins remains the major cause of AF recurrence. Novel ablation tools, such as balloon technologies or alternative energy sources, might help to overcome this limitation. Patients with non-paroxysmal AF and with AF recurrence might benefit from alternative ablation strategies. However, further studies are warranted to further improve our knowledge of the underlying mechanisms of AF and to obtain long-term clinical outcomes on new ablation techniques.